Numerical Solutions Of Volterra Integral Equations Using Legendre Polynomials - Rahman, Md Azizur; Islam, Md Shafiqul (GANIT: Journal of Bangladesh Mathematical Society, 2013)
In this paper, Legendre piecewise polynomials are used to approximate the solutions of linear Volterra integral equations. Both second and first kind integral equations with regular as well as weakly singular kernels are considered. A matrix formulation is given for linear Volterra integral equations by the technique of Galerkin method. Numerical examples are considered to verify the accuracy of the proposed derivations, and the numerical solutions in this paper are also compared with the existing methods in the published literature. DOI: http://dx.doi.org/10.3329/ganit.v32i0.13643 GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 32 (2012) 29 35